De imigrantes na Amazônia a nobres em Portugal: Visconde de Monte Redondo, Visconde de Penedo e Visconde de Nazaré - QUARESMA, Luís Augusto Barbosa (Universidade Federal do Pará, 2023)
The dynamics that are found in the trajectory of the cities present them as elements in constant transformation, effervescence, movements, interruptions and continuities that (re)write themselves as the time goes by. Such scenario can be found in the city of Belém, capital of the state of Pará, which, in the period between 1870 and 1914, inserts itself in the period called Belle Époque, when significant changes occurred, which marked the trajectory of the city and of the people that lived in it towards the modernity that was materializing from the 19th century to the 20th century. In this scenario, there’s a significant flux of European immigrants that moved to the Amazon region, mainly, in the case of this study, of Portuguese people. In this context, this thesis has the goal of understanding the trajectory of Joaquim Antonio de Amorim (Viscount of Monte Redondo), Antonio José Antunes Sobrinho (Viscount of Penedo) and Bernardo Antonio Nunes (Viscount of Nazaré), who stablished themselves at the capital of Pará during the heyday of the rubber market. A diversified theoretical basis was used, which gave support to the construction of the trajectory of these individuals, as well carrying out documental and iconographic research, based on newspapers and official sources, such as reports, testimonies, inventories in institutions with collections that collaborated with this work. The results showed that such subjects had relevant roles in the socioeconomical dynamic of Belém, got involved with cultural, structural and sanitary changes of the city, which brought them to economical and sociopolitical prosperity. They left marks in the city and in the Portuguese community, thus, this thesis reveals the importance of these people to the existing Portuguese community in Pará and to the other people that transited in the Amazon city between the second half of the 19th century and the beginning of the 20th century.